Mitophagy: An Emergence of New Player in Alzheimer’s Disease - Sharma, Bunty; Pal, Deeksha; Sharma, Ujjawal; Kumar, Aman (Frontiers in Molecular Neuroscience, 2022)
Mitochondria provide neurons not only energy as ATP to keep them growing, proliferating and developing, but they also control apoptosis. Due to their high bioenergetic demand, neurons which are highly specific terminally differentiated cells, essentially depend on mitochondria. Defective mitochondrial function is thus related to numerous age-linked neurodegenerative ailments like Alzheimer’s disease (AD), in which the build-up of impaired and malfunctioning mitochondria has been identified as a primary sign, paying to disease development. Mitophagy, selective autophagy, is a key mitochondrial quality control system that helps neurons stay healthy and function by removing undesired and damaged mitochondria. Dysfunctional mitochondria and dysregulated mitophagy have been closely associated with the onset of ADs. Various proteins associated with mitophagy were found to be altered in AD. Therapeutic strategies focusing on the restoration of mitophagy capabilities could be utilized to strike the development of AD pathogenesis. We summarize the mechanism and role of mitophagy in the onset and advancement of AD, in the quality control mechanism of mitochondria, the consequences of dysfunctional mitophagy in AD, and potential therapeutic approaches involving mitophagy modulation in AD. To develop new therapeutic methods, a better knowledge of the function of mitophagy in the pathophysiology of AD is required.